Innovation in Population Administration Services through BERKAT (Bereavement Visit Based Death Certificate Delivery) in Sukoharjo Urban Village, Probolinggo City - Veronica Sri Astuti N; Eko Yudianto Yunus; Andre Kurniawan (The Future of Education Journal, 2026)
This study examines the innovation of population administration services through the BERKAT program (Bereavement Visit-Based Death Certificate Delivery) in Sukoharjo Village, Probolinggo City. This program emerged as a response to the low public awareness in processing death certificates and the limitations of conventional service patterns that were considered less responsive to the socio-emotional conditions of the community. This study employed a descriptive qualitative method with data collected through participatory observation, semi-structured in-depth interviews, and documentation. Informants were selected purposively according to the needs of the study. The analysis was conducted using Rogers' diffusion of innovation theory, encompassing five dimensions: relative advantage, compatibility, complexity, trialability, and observability. The results indicate that the BERKAT program has significant relative advantage through an integrated one-stop service system and a proactive home-visit approach to bereaved families. The program is considered compatible with community needs, has a manageable level of complexity, is easy to trial, and its benefits are directly observable by the public. Successful implementation is supported by solid cooperation among stakeholders and human resources that are both technically competent and empathetic. Obstacles encountered include limitations in information technology infrastructure and the number of staff on the internal side, as well as low public awareness and incomplete required documents on the external side. This study confirms that public service innovation that combines administrative efficiency with social empathy values proves more effective in addressing the real needs of the community, particularly at the village administrative level.